2015
DOI: 10.1016/j.cgh.2014.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Upper Gastrointestinal Cancers in Patients With Gastroesophageal Reflux Disease After a Negative Screening Endoscopy

Abstract: Background & Aims Practice guidelines recommend a 1-time screening endoscopy for patients with gastroesophageal reflux disease (GERD) who are at high risk for Barrett’s esophagus or malignancy. However, little is known about the risk of cancer in patients with negative findings from screening endoscopies. Methods We conducted a retrospective cohort study using data from 121 Veterans Health Administration facilities nationwide to determine the incidence rate of esophageal adenocarcinoma (EA) separately, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Prevalence per country is presented in Figure 3 . Within individual continents, there was moderate heterogeneity between studies (I 2 <65%), which was significant ( p = 0.04) in Asian studies at age limits of 45 years and 50 years, and in Europe at a 60-year age limit ( Supplemental Figure 1 ). Univariate meta-regression analysis using covariates ‘presence of alarm symptoms’, ‘malignancy location’, and ‘sample size n ⩾ 1000’ did not reveal a potential source for heterogeneity (not significant) ( Supplemental Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prevalence per country is presented in Figure 3 . Within individual continents, there was moderate heterogeneity between studies (I 2 <65%), which was significant ( p = 0.04) in Asian studies at age limits of 45 years and 50 years, and in Europe at a 60-year age limit ( Supplemental Figure 1 ). Univariate meta-regression analysis using covariates ‘presence of alarm symptoms’, ‘malignancy location’, and ‘sample size n ⩾ 1000’ did not reveal a potential source for heterogeneity (not significant) ( Supplemental Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Confidence intervals (CIs) were calculated according to the Wilson score method. Heterogeneity was quantified using the I 2 measure if more than three studies were included. In cases where heterogeneity was encountered, univariate meta-regression analysis was used to explore the influence of alarm symptoms, location of malignancy, and sample size as a source for heterogeneity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Reviews of patients diagnosed with upper gastrointestinal cancer a short time after a negative upper endoscopy found that the index upper endoscopy in most of these patients demonstrated suspicious or unclear findings that were neglected by the endoscopist or the reviewing pathologist. 22,23 Approximately 30% of esophageal adenocarcinomas arising from Barrett's esophagus are now considered to be post-endoscopy tumors. 24 Regarding colonoscopy, several quality indicators have been developed and implemented after the introduction of general colorectal cancer screening programs, such as adenoma detection rate of the performing endoscopist.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 6 ] Additionally, recent studies have demonstrated that while screening endoscopy can be performed on patients with GERD, the risk of developing adenocarcinoma in a patient with negative screening endoscopy is very low, such that routine follow up endoscopies is not necessary. [ 7 8 ] Nonetheless, there is a reported 7.8% inaccuracy rate of endoscopy missing esophageal cancer during endoscopy. [ 9 ] Thus, no routine endoscopic surveillance strategy has been established for esophageal cancer.…”
Section: Screening Esophageal Cancermentioning
confidence: 99%